О фауне жуков семейства Coccinellidae лесной и лесостепной зон левобережной Украины - Мизер, А.В. (Вестник зоологии, 1969)
In forest and forest-steppe zones of the Left-bank Ukraine 58 species (30 genera) of coccineljidae were registered. Thirteen species of them to the share of which about 89% falls of the general quantity of the gathered beetles are sharply distinguished by their amount. From the rest 43 species 14 ones are usual for the given territory, 20 — rare and 9 — very rare.